2009
DOI: 10.5539/ass.v4n12p27
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Housing in Sabah, Malaysia: A Regression Analysis

Abstract: Low-cost housing plays a vital role in the development process especially in providing accommodation to those who are less fortunate and the lower income group. This effort is also a step in overcoming the squatter problem which could cripple the competitive drive of the local community especially in the state of Sabah, Malaysia. This article attempts to look into the influencing factors to low-cost housing in Sabah namely the government's budget (allocation) for low cost housing projects and Sabah's total pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Sabah is chosen as one of the less developed states in Malaysia. Sabah somewhat has a large number of housing projects in East Malaysia out of a growing number of mortgage transactions, and in wider prime areas (Mulok and Kogid, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Sabah is chosen as one of the less developed states in Malaysia. Sabah somewhat has a large number of housing projects in East Malaysia out of a growing number of mortgage transactions, and in wider prime areas (Mulok and Kogid, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Sabah is chosen, as it has a bright potential for current and future housing and property market in East Malaysia. Essentially, Sabah relatively has a large number of housing projects compared with Sarawak (Mulok and Kogid, 2008). It is also reported that the national house price index for Sabah is the highest in Malaysia, rising to 217.2 in 2010 from 132.5 in 2006, an increase of 63.9 per cent over four years (New Sabah Times, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…A general view through graphical displays, as shown in FIGURE 1, both economic growth (real GDP) and tourist arrival tend to increase over time with slightly changes occurring within the years 1997-1998and 2007-2008for real GDP, and in 1998-2002 for the tourist arrival. Changes in real GDP are mainly due to the Asian financial crisis that occurred in the mid 1997 and the global financial crisis in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in real GDP are mainly due to the Asian financial crisis that occurred in the mid 1997 and the global financial crisis in 2008. Changes in the tourist arrival, on the other hand, are mainly due to the Asian financial crisis in the mid 1997 and world electronics demand crisis as well as the September 11 incident in USA in 2001 (Mulok & Kogid 2008).…”
Section: Introductionmentioning
confidence: 99%